ANALYSIS OF THE EFFECT OF COMPETENCE OF HUMAN RESOURCES, APPLICATION OF GOVERNMENT ACCOUNTING STANDARDS, REGIONAL ACCOUNTING SYSTEMS AND UTILIZATION OF INFORMATION TECHNOLOGY ON THE QUALITY OF CITY GOVERNMENT FINANCIAL STATEMENTS BINJAI WITH CONTROL SYST - barus, syarifuddin (International Journal of Public Budgeting, Accounting and Finance, 2018)
This study aims to analyze the influence of competencies in human resources, the application of government accounting standards, regional financial accounting systems and the use of information technology on the quality of Binjai City Government financial reports with the government's internal control system as a moderating variable. This type of research is associative research that is causal. The population and sample in this study were the Heads of Regional Work Units (SKPD), SKPD Financial Administration Officers and Expenditure of SKPD Expenditures totaling 99 (ninety nine) people at 33 (thirty three) SKPDs in Binjai City. Hypothesis testing uses multiple linear regression with a coefficient of determination, F test and t test. The results of this study indicate that simultaneously the competency variables of human resources, the application of government accounting standards, regional financial accounting systems and utilization of information technology have a significant positive effect on the quality of Binjai City Government financial reports, while partially the competency variables of human resources and utilization of information technology are influential a significant positive effect on the quality of the financial statements of the Binjai City Government and the variable implementation of government accounting standards and the regional financial accounting system does not affect the quality of the financial statements of the Binjai City Government.While the government's internal control system is not able to moderate the relationship between the competence of human resources, the application of government accounting standards, regional financial accounting systems and the use of information technology with the quality of the financial statements of the Binjai City Government.